Beyond panaceas in water institutions - Meinzen-Dick, Ruth S. (Proceedings of the National Academy of Sciences, 2007)
The past 50 years of water policy have seen alternating policies emphasize the state, user groups, or markets as essential for solving water-management problems. A closer look reveals that each of these solutions has worked in some places but failed in others, especially when policies attempted to spread them over too many countries and diverse situations. A study of the variable performances of user groups for canal irrigation in India illustrates the factors that affect institutional performance. Research that identifies the critical factors affecting irrigation institutions can lead to sustainable approaches that are adapted to specific contextual attributes.